Integrating Penal and Non-Penal Approaches in Addressing Child Grooming in Indonesia - Hanna Fitri Raziah; Padlilah; CSA Teddy Lesmana (AL-MANHAJ: Jurnal Hukum dan Pranata Sosial Islam, 2026)
This study examines criminal law policy on child grooming in the context of age restrictions for internet users in Indonesia. The main problem lies in the absence of explicit regulation of child grooming as a stand-alone offense. However, this crime develops through psychological manipulation, gradual digital communication, identity concealment, emotional exploitation, and requests for sexual content involving children. Previous studies have discussed online child sexual exploitation and child protection in digital spaces, yet they have not sufficiently connected age restriction policy with criminal law reform on child grooming. This study offers a novel perspective by positioning age restriction as a non-penal preventive instrument that must be integrated into penal policy. Using a normative juridical method with statutory and conceptual approaches, this study analyzes legal materials qualitatively through Barda Nawawi Arief's criminal law policy theory and Lawrence M. Friedman's legal system theory. The findings show that Indonesia's criminal law regulation remains partial because relevant provisions are scattered across the Child Protection Law, the ITE Law, the TPKS Law, and the Pornography Law. Age restriction policies under Government Regulation Number 17 of 2025 and Ministerial Regulation Number 9 of 2026 are preventive but still administrative in character. This study contributes to criminal law scholarship by recommending the formulation of child grooming as a specific offense and the integration of penal and non-penal approaches.